Literacy Teacher Educators
XX, 206 p.
Keywords: Literacy Teacher Educators: Preparing Teachers for a Changing World brings together the perspectives of 26 literacy/English teacher educators from four countries: Canada, U.S., UK, and Australia. In this unique text the contributors, of whom many are renowned experts in critical literacy and multiliteracies, provide readers with an overview of trends in literacy/English teacher education. The chapters begin with authors’ personal stories and current research, giving readers insight into the personal and professional worlds of the contributors. Included in each chapter is a rich description of approaches to literacy instruction in teacher education. These exemplary teacher educators show in concrete detail how they are addressing our evolving understanding of literacy . This timely text, written in a highly engaging style, will be of value to teacher educators throughout the world. I have never read anything quite like this book. It contains explicit representations of the conceptual frames and work of distinguished literacy teacher educators at various stages in their careers, accounts that provide a strong counter-narrative to the mainstream discourse in policy and education, that fully embrace the uncertainties and complexities of practice." From the Forward by Susan L. Lytle, Professor Emerita of Education in the Graduate School of Education, University of Pennsylvania.